If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 6(x + y) + y + 3(x + 3) 0 = (x * 6 + y * 6) + y + 3(x + 3) 0 = (6x + 6y) + y + 3(x + 3) Reorder the terms: 0 = 6x + 6y + y + 3(3 + x) 0 = 6x + 6y + y + (3 * 3 + x * 3) 0 = 6x + 6y + y + (9 + 3x) Reorder the terms: 0 = 9 + 6x + 3x + 6y + y Combine like terms: 6x + 3x = 9x 0 = 9 + 9x + 6y + y Combine like terms: 6y + y = 7y 0 = 9 + 9x + 7y Solving 0 = 9 + 9x + 7y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 0 + -9x = 9 + 9x + -9x + 7y Remove the zero: -9x = 9 + 9x + -9x + 7y Combine like terms: 9x + -9x = 0 -9x = 9 + 0 + 7y -9x = 9 + 7y Divide each side by '-9'. x = -1 + -0.7777777778y Simplifying x = -1 + -0.7777777778y
| 2y-8=10y+24 | | 4x=2x-14 | | 500-20x=0 | | -8n=42 | | -3.6h=10.8 | | 7x+20=8x+2 | | =9+2(x+7)+7(y+2) | | =2y+8(y+1)+5(x+5) | | 4e+-3e+-2e=1+-9 | | Y=5x^3-17x^2-12x | | 23+24a=29+23a | | 5s-1-6s^2=0 | | 5a(3a-5)(5a-1)=0 | | -(2f-4)=-4-f+2 | | 3z+5+2z=13+3z | | =3(x+y)+4(y+x) | | 14+3n=8n-3+10x | | 2x^2+12+9x-18-3x-4x=0 | | x+x+1+x+2=-3.75 | | 11+3x-7=6x+-3x | | 9w-18w-18w+36= | | =6+6(x+4)+15y+x | | -1(x+4)+5=4x+1-5x | | 14+4x+6=8x | | -19x+23y=-3 | | 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= |